A study of revit dynamo for precast mould’s dimension and Bentley Synchro for quality inspection - Toh, Shi Rong (Nanyang Technological University, 2023)
The construction industry is a sector of the economy that is involved in the design, planning, construction, and maintenance of building and infrastructure. It is a complex and diverse industry that encompasses a wide range of activities, including architecture, engineering, construction management, project management, and building trades such as carpentry, plumbing, electrical work, and many others. The construction industry plays a vital role in the growth and development of communities and economies around the world. It provides employment opportunities for millions of people and contributes to the creation of new homes, commercial buildings, transportation systems, and other essential infrastructure. The industry is often a key indicator of economic activity, as increased construction activity is often associated with increased economic growth. However, the construction industry also faces many challenges, such as project delays, cost overruns, safety concerns, manpower shortages, and environmental impact. Advances in technology and innovation are helping to address some of these challenges, such as the use of Building Information Modelling (BIM), prefabrication, and sustainable building practices. The industry is also increasingly embracing digitalization and automation to improve efficiency, productivity, and quality. Singapore can therefore leverage on emerging technologies such as Light Detection and Ranging technology (LiDAR), Building Information Modelling (BIM) using Revit and Synchro to further increase productivity and quality in construction. This study aims to explore on two aspects. Firstly, exploration on the potential of using LiDAR technology and Revit Dynamo to automate the process of dimension generation. Secondly, exploration on Bentley Software – Synchro to enhance the quality inspection process with Quality Inspection Form and Quality Inspection Workflow. Past works on LiDAR and BIM assisted inspection process will be review before proposing a way to add dimensions on LiDAR points and develop a workflow for quality inspections.